ReGo-Cardio: An Innovative Low-Impact Cardio Exercise App for Heart Health Rehabilitation for Coronary Heart Disease Patients in Gorontalo - Suleman, Ibrahim; Abdulkadir, Widy Susanti; Tumaloto, Ella H (Jambura Nursing Journal, 2025)
Coronary heart disease (CHD) is one of the leading causes of death among the elderly, particularly in Indonesia, with a significant increase in prevalence as age advances. This condition is often accompanied by a decline in physical capacity, quality of life, and an increased risk of other health complications. Cardiac rehabilitation is one of the solutions to improve the physical condition and quality of life of CHD patients. This study aims to evaluate the effectiveness of the REGO-CARDIO application in a cardiac rehabilitation program for elderly CHD patients in Gorontalo. A total of 30 patients were recruited to participate in the rehabilitation program for 4 weeks, with pre-test and post-test measurements for variables such as systolic blood pressure, diastolic blood pressure, resting heart rate, aerobic capacity (distance covered in a 6-minute walk test), and quality of life (measured using the KCCQ instrument). The results of the study showed significant reductions in systolic and diastolic blood pressure, as well as resting heart rate after participating in the rehabilitation program. Significant improvements were also observed in aerobic capacity and quality of life. All these changes demonstrated statistically significant p-values (p < 0.05), indicating that the REGO-CARDIO application is effective in improving the physical condition and quality of life of CHD patients. This study suggests that technology-based cardiac rehabilitation can be an efficient alternative, accessible to more patients, particularly in areas with limited medical facilities.